(untitled) (PROKLA. Journal of Critical Social Science, 2014)
When at the latest with the crises of the financial markets a new focus on class issues was set on Marxian theorists’ agenda, there is the question, how to cope with it. The idea of class is central for Marxian theories, but enigmatic and controversal at the same time. Reason enough to review and to reconsider as well the dynamics of the discussions within the last 50 years and to focus the sets of problems and unanswered questions.